Mixture design and physicochemical characterization of amino acid-based DEEP eutectic solvents (AADES) for sample preparation prior to elemental analysis - Guimarães, Taciana G.S. [UNESP]; Andrade, Daniel F.; Santana, Ana P.R.; Moser, Poliana [UNESP]; Ferreira, Sabrina S. [UNESP]; Menezes, Iohanna M.N.R.; Amaral, Clarice D.B.; Oliveira, Andrea; Gonzalez, Mario H. [UNESP] (Elsevier, 2022)
Amino acid-based deep eutectic solvents (AADES) represent a new subclass of deep eutectic solvents (DES) in which at least one of the components must be an amino acid, offering advantages such as low toxicity, biodegradability and low cost. In this work, β-alanine was used as hydrogen bond acceptor (HBA) in the preparation of a total of 30 AADES mixtures, with the hydrogen bond donor (HBD) being malic acid (AADES 1), citric acid (AADES 2), or xylitol (AADES 3), together with the addition of water. A restricted mixture design was employed to optimize the ideal proportions of the AADES components, which were determined as (% m m−1) 12.50 for β-alanine, 43.75 for the HBD component, and 43.75 for water (represented by molar ratio 1:2:17 for the three AADES mixtures), with lower values of density and viscosity being the desired responses. Solvents that have low density and viscosity provide greater efficiency in sample preparation procedures, due to faster mass transfer. The highest density and viscosity values were found for AADES 2, due to the greater presence of carboxyl groups in the molecular structure of citric acid, allowing the formation of more hydrogen interactions. The Herschel-Bulkley model provided the best fit to the rheological behavior of the AADES, with AADES 2 showing the highest consistency index. Solvatochromic analyses showed that these solvents had high polarity. Fourier transform infrared (FTIR) spectroscopy analysis revealed hydrogen interactions between the precursor components, confirming formation of the AADES. Thermal analysis revealed the ideal working temperature ranges for applying these solvents in sample preparation, with thermogravimetry (TGA) indicating maximum temperatures of 130 °C for AADES 1 and 150 °C for AADES 2 and AADES 3. Differential scanning calorimetry (DSC) revealed the minimum temperatures at which the solvents remained liquids, which were −13 °C for AADES 1, –22 °C for AADES 2, and −21 °C for AADES 3. Therefore, these AADES were shown to be promising solvents for application in sample preparation, being suitable for the extraction of polar compounds, as well as metals and semimetals. An EcoScale study was carried out, which confirmed that the preparation of the solvents could be considered an excellent green synthesis.
Keywords: ICP-MS; ICP-OES; Mixture design; Physicochemical properties; Sample treatment